2005
DOI: 10.1590/s0100-879x2005000400014
|View full text |Cite
|
Sign up to set email alerts
|

Maternal aggression in Wistar rats: effect of 5-HT2A/2C receptor agonist and antagonist microinjected into the dorsal periaqueductal gray matter and medial septum

Abstract: The objective of the present study was to assess the role of the 5-HT 2A/2C receptor at two specific brain sites, i.e., the dorsal periaqueductal gray matter (DPAG) and the medial septal (MS) area, in maternal aggressive behavior after the microinjection of either a 5-HT 2A/2C receptor agonist or antagonist. Female Wistar rats were microinjected on the 7th postpartum day with the selective agonist α-methyl-5-hydroxytryptamine maleate (5-HT 2A/2C ) or the antagonist 5-HT 2A/2C , ketanserin. The agonist was inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 18 publications
0
14
0
4
Order By: Relevance
“…11 Although binding studies found a higher density of these receptors in limbic areas, it is interesting to note that α-Methyl-5-hydroxytryptamine maleate, the 5-HT 2A/2C receptor agonist, is more effective in reducing the aggressive behavior in mesencephalic rather than in diencephalic or telencephalic areas.…”
Section: Discussionmentioning
confidence: 99%
“…11 Although binding studies found a higher density of these receptors in limbic areas, it is interesting to note that α-Methyl-5-hydroxytryptamine maleate, the 5-HT 2A/2C receptor agonist, is more effective in reducing the aggressive behavior in mesencephalic rather than in diencephalic or telencephalic areas.…”
Section: Discussionmentioning
confidence: 99%
“…На настоящий момент известно, что генотипы 5-HT2A связаны с депрессией [14,[27][28][29]35], тревогой [65,72], агрессивно-импульсивными чертами личности [6,25,36,45,46,54,55,59,61,62,64,66], сокращением гладкомышечных сосудов [19,38,42], антитромботиче-ской активностью [5,31,42,47], воспалительными реак-циями артерий [18,26,44,74]. Все вышеописанные про-цессы связаны с патогенезом ИБС [3], вследствие этого мы решили изучить связь вариантов гена 5-HT2A (А-1438G) с дебютом ИБС.…”
Section: работы по изучению связи генотипов гена 5-httunclassified
“…Имеется множество сведений о том, что 5-HT2A-рецептор участвует в формировании агрессивно-импуль-сивных черт [6,25,32,36,45,54,55,59,61,62,64,66]. Су-ществуют исследования, которые эту связь не обнаружи-ли [10,17].…”
Section: дискуссияunclassified
“…Agents that affect these neurochemicals are known to cause serious side effects and hence the limitation of their usefulness in aggression 59 .…”
Section: Other Neurotransmitters Associated With Aggressionmentioning
confidence: 99%